Agua Lamp / Muhammad Hafizul Amri Mohamad Norami - Mohamad Norami, Muhammad Hafizul Amri (2020)
The name “Agua” is derived from the Spanish language and it means “water”. Based on the important components for this innovation technology. Nowadays, people are concerned about power saving. Our Agua Lamp will provide light without using electricity. We can save a lot of electricity Eco-friendly to the public community especially for students and backpackers. The simple design and discreet colours of Agua Lamp make it very suitable for any space bedroom, living room, bathroom or even your working environment. This lamp is powered by water during chemical reaction. The main reason that makes this lamp so original is that it functions simply with the help of the power of water. Namely, this cordless lamp needs just a little bit of water and a hydroelectric battery. There will be a variety of designs according to customers' demand. We will introduce this new technology to the public, in order to reduce electrical usage in domestic daily due to global warming nowadays. The lampshade is made of sanded blow glass, on the top of it there is a part made of bioplastic where the battery is set and where you pour the water, with an interesting steel switch, while the light comes from the warm white led strips.